Bone Marrow Mesenchymal Stem Cell-Derived Extracellular Vesicles Carrying circ_0050205 Attenuate Intervertebral Disc Degeneration. (5th July 2022) - Yu, Xiao-Jun; Liu, Qi-Kun; Lu, Rui; Wang, Shan-Xi; Xu, Hao-Ran; Wang, Ying-Guang; Bao, Yuan; Jiang, Yong-Qiao; Li, Meng-Wei; Kang, Hao
Abstract : Objective . It has been reported that bone marrow mesenchymal stem cells (BMSCs) are a potential source of autologous stem cells to support the nucleus pulposus (NP) regeneration in intervertebral disc degeneration (IDD). Herein, we aim to study the mechanism underlying the effects of BMSC-derived extracellular vesicles (BMSC-EVs) on nucleus pulposus cells (NPCs) in IDD. Methods . EVs were isolated from BMSCs. An IDD model was surgically established in C57BL/6J mice. NPCs were exposed to tBHP to establish an IDD cell model. RNA sequencing was performed to identify differentially expressed circRNAs in NP tissues harvested from mice with IDD. Interactions among circ_0050205, miR-665, and GPX4 were validated, and different interventions were used to study the roles of these molecules in NPC biological functions. Results . BMSC-EVs promoted NPC survival and inhibited NPC apoptosis and extracellular matrix (ECM) degradation. circ_0050205 expression was downregulated in the NP tissues of IDD mice, and BMSC-EVs facilitated NPC survival and suppressed ECM degradation in NPCs by transferring circ_0050205. circ_0050205 sponged miR-665 and upregulated GPX4 expression. BMSC-EVs expressing circ_0050205 promoted NPC survival-inhibited ECM degradation in NPCs and alleviated IDD in mice via the miR-665/GPX4 axis. Conclusion . In conclusion, BMSC-EVs promoted NPC survival-inhibited ECM degradation in NPCs and attenuated IDD progression via the circ_0050205/miR-665/GPX4 axis.